قضايا السرد وأبعاده في الأعمال الأدبية للكاتب أحمد رضا حوحو - بومعزة, نوال (جامعة الوادي - university of Eloued, 2021)
تهدف هذه الدراسة إلى محاولة رصد أهم القضايا التي اضطلع بها السرد في نصوص الكاتب الجزائري أحمد رضا حوحو، الذي جاهد بقلمه ونفسه في سبيــل نشر الوعي والثقافة، فتحوّلت نصوصه إلى رسائل مليئة بالأهداف السامية، بأسلوب سردي يهدف بالدرجة الأولى إلى تحقيق المنفعة والصلاح للفرد والمجتمع.وقد حاولت من خلال هذه الدراسة الإجابة عن الإشكالات المعرفية الآتية: ماهي أهم قضايا السرد التي احتوتها نصوص الكاتب أحمد رضا حوحو؟ وما خصوصية السرد في كتاباته؟ ولتحقيق القدر اليسير من التحليل استعنت بالقراءة الموضوعاتية في البحث عن القضايا والأبعاد في أعمال الكاتب مع توظيف منجزات السرديات الحديثة، خاصة في تحليل الشخصيات، وعرض خصائص البناء السردي. This study aims to try to monitor the most important issues carried out by the narrative in the texts of the Algerian writer Ahmed Reda Houho, who struggled with his pen and himself to spread awareness and culture, and his texts turned into messages full of lofty goals, in a narrative style aimed primarily at achieving benefit and good for the individual and society. Through this study, I tried to answer the following cognitive problems: What are the most important narrative issues contained in the texts of the writer Ahmed Reda Houho? What is the specificity of the narrative in his writings? To achieve a little analysis, I used thematic reading in the search for issues and dimensions in the author's work while employing the achievements of modern narratives, especially in character analysis, and presenting the specificity of narrative construction.
مقال
Keywords: قضايا، السرد، منفعة، الوعي ، الكتابة; Issues, narrative, utility, awareness, writing.